PETA MUTU MADRASAH ALIYAH DI INDONESIA BAGIAN BARAT TAHUN 2013: MAPPING THE MADRASAH ALIYAH QUALITY IN WESTERN INDONESIA IN 2013 - M Amin Thaib BR (Balai Penelitian dan Pengembangan Agama Jakarta, 2014)
This article provides the results of a study on the quality of Madrasah Aliyah (MA) in Western Indonesia based on the results of accreditation conducted by Badan Akreditasi Nasional (National Accreditation Agency) in 2013. There are 3,101 MA, consisting of 383 state madrasah and 2,718 private madrasah,spread throughout 13 provinces in Western Indonesia. The study found that 63 percent of the total madrasah in Western Indonesiahas met accreditation standards, and 44 percent of them are accredited with A and B degrees. State madrasah show better performance than their private counterparts. Out of 383 madrasah, 79 percent madrasah has been accredited and 73 percent of them gained A and B degrees. Meanwhile, only 60 percent of 2,718 private madrasah has met accreditation standards, with 40 percent of them obtaining A and B degrees. In addition, out of 13 provinces, only in 5 provinces where MA have already achieved the targets of the government development objectives. The five provinces include West Java, North Sumatera, Jakarta, Riau Islands, and Bangka-Belitung. The lack of laboratory becomes one of the primary problems that most madrasah face. Key Words: Madrasah quality, accreditation, Western Indonesia. Tulisan ini menyajikan hasil penelitian terhadap kualitas Madrasah Aliyah (MA) di Indonesia Bagian Barat (IBB) yang didasarkan pada hasil akreditasi Badan Akreditasi Nasional tahun 2013. Madrasah Aliyah (MA) di IBB adalah 3.101, hampir separuh (46.53%) dari jumlah MA se Indonesia (6.664). Penelitian ini menemukan, bahwa 63% MA sudah terakreditasi, 44% nya pada peringkat A & B. Madrasah Aliyah Negeri menunjukkan lebih baik dari Madrasah Swasta. Dari 383 madrasah (lebih dari separuh MAN se Indonesia), 79% sudah memenuhi standar, dan 73%-nya sudah pada peringkat A & B. Sementara MA Swasta (MAS) hanya 60% yang sudah memenuhi standar dari sebanyak 2.718 (hampir setengah dari MAS se Indonesia), dan baru 40% pada peringkat A &B. Dari MA di 13 provinsi, baru di 5 Provinsi (Jabar, Sumut, DKI Jakarta, Kep. Riau, dan Babel) yang sudah memenuhi target sasaran pembangunan. Kurangnya laboratorium menjadi salah satu problem utama yang dihadapi madrasah dalam hal akreditasi. Kata Kunci: Mutu madrasah, akreditasi, Indonesia Bagian Barat.